The Relationship Between (sub)national Identity, Citizenship Conceptions, and Perceived Ethnic Threat in Flanders and Wallonia for the Period 1995–2020: A Measurement Invariance Testing Strategy - Billiet, Jaak; Meeusen, Cecil; Abts, Koen (Frontiers in Political Science, 2021)
This article examines the relationship between (sub)national identity and attitudes towards immigrants in the multinational context of Belgium. We extend our previous studies by analysing a longer time period (1995–2020) and by making a strong case for the idea that measurement invariance testing and theoretical meaningfulness are closely intertwined. To examine whether and how the relationship between (sub)national identity and perceived ethnic threat has changed over time and between regions, we first test for metric invariance of the latent concepts. Using data from the Belgian National Election Studies, we illustrate that evaluating invariance of measurements is a necessary condition for comparative research, but also that measurement equivalence testing should be considered as an empirical guide showing researchers where substantial conclusions should potentially be revisited and theoretical validity rethought. Next, we verify whether the relationship between (sub)national identity and perceptions of ethnic threat across subnational units can be attributed to different conceptions of community membership -in terms of ethnic and/or civic citizenship conceptions- in Flanders and Wallonia. While we expected that a strong identification with Flanders would primarily be related to an ethnic citizenship representation, and as a result, stronger feelings of threat towards immigrants; we expected that a strong identification with Wallonia would primarily be related to a civic representation of the nation and therefore lower feelings of threat. Thanks to our thorough invariance testing strategy, the conceptualisation and measurement of (sub)national identity had to be adjusted in Wallonia, and the hypotheses had to be qualified.